2022
DOI: 10.1371/journal.pone.0272821
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of triple dose albendazole treatment for soil-transmitted helminth infections

Abstract: In Malaysia, soil-transmitted helminth (STH) infections still persist among indigenous communities. In the past, local studies have focused mostly on epidemiologic aspects of STH infections with a scarcity of information on the efficacy of deworming treatment. The present study consisted of 2 phases: a cross-sectional phase on current epidemiological status and risk factors of STH infections and a longitudinal study over 6 weeks on triple dose albendazole efficacy against STH infections. A total of 253 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
4
14
0
2
Order By: Relevance
“…A study among Rwandan children showed an overall cure rate of 88.6% and an ERR of 75.4% by wet mount microscopy, and in our study the CR was 90.7% [ 22 ].The cure rates depend on the individual parasitic load and the presence of parasites in the environment, which could cause reinfection. In addition, the cure rate depends on the number of doses, quality of the drug, and dosage [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study among Rwandan children showed an overall cure rate of 88.6% and an ERR of 75.4% by wet mount microscopy, and in our study the CR was 90.7% [ 22 ].The cure rates depend on the individual parasitic load and the presence of parasites in the environment, which could cause reinfection. In addition, the cure rate depends on the number of doses, quality of the drug, and dosage [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, gut microbiota helps in metabolising albendazole and influence drug bioavailability and efficacy on infected individuals. 35,36 However, a huge diversity and functional capacity of human gut microbiome perform in various ways regarding the protection against pathogen overgrowth, inflammation, influence host-cell proliferation, biosynthesis of vitamins, and react differently to drugs and their metabolism. 37 Similarly, anthelmintic treatment could affect the gut microbiome through acting on intestinal protozoa, which have close interaction with gut microbiome, thus leading to improvement in the nutritional status of the children and to combat the multi-micronutrient deficiencies including zinc.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Albendazole restrains the helminths glucose uptake and energy production, and ultimately exerts a spastic or paralytic effect on the worm. In this regard, gut microbiota helps in metabolising albendazole and influence drug bioavailability and efficacy on infected individuals 35,36 . However, a huge diversity and functional capacity of human gut microbiome perform in various ways regarding the protection against pathogen overgrowth, inflammation, influence host‐cell proliferation, biosynthesis of vitamins, and react differently to drugs and their metabolism 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that anthelmintic drugs have varying levels of effectiveness against different species of STH, and they are particularly ineffective against Trichuris trichiura when using single-dose treatments [50]. Previous comparative studies have shown that a triple-dose regimen is more effective in treating STH than a single or double-dose regimen, particularly in co-endemic areas where all three STH species are prevalent [51][52][53]. Additionally, a study found that the combination therapy of ivermectinalbendazole had good tolerability and higher efficacy against T. trichiura compared to the current standard single-dose albendazole treatment, supporting its use in PC programs [54].…”
Section: Fig 9: Risk Factors Associated With Soil-transmitted Helmint...mentioning
confidence: 99%